PERSEPSI KINESTETIK, KOORDINASI MATA TANGAN DAN MOTIVASI TERHADAP JUMP SMASH - Edy Dharma Putra Duhe; Arief Ibnu Haryanto (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
Abstract This study aims to determine the relationship between kinesthetic perception, hand eye coordination and motivation on volleyball jump smashes in volleyball athletes in Gorontalo City. The research method used is descriptive correlational. The population used was volleyball athletes in Gorontalo City, amounting to 15 people with samples taken using total sampling method. The data collection technique in this study is a one-shoot model or one-time data collection and data analysis techniques use product moment correlation. From the results of the research on the relationship between kinesthetic perception and volleyball jump smash, the r count is 0.87> 0.541. Then the results of the research on the relationship between hand eye coordination and volleyball jump smash show that the r count is 0.71> 0.541 motivation with a volleyball jump smash, the r count was 0.80> 0.541. Meanwhile, the joint relationship between kinesthetic perception, hand eye coordination and motivation with a volleyball jump smash obtained a calculated r value of 0.82> 0.541. The conclusion of this study is that there is a significant co-relationship between kinesthetic perception, hand eye coordination and motivation with the volleyball jump smash.